Local government management - Benavides, Teodoro J.; Valcik, Nicolas A. (Routledge, 2023)
In a recent paradigm shift, local governments find themselves shouldering more responsibility for day-to-day governance and crisis management, thanks to regulations and federal spending cuts. While twenty years ago a book on local government administration might have been considered complete with chapters on budgeting, public personnel management, productivity and responsivity, and community engagement, any discussion of local government must now also include resiliency, emergency management, climate change, smart cities, social media, and infrastructure funding. Bringing together key voices from the academic and public sectors, Local Government Management offers techniques and insight into how local government can most effectively lead and manage their resources in an evolving political - and environmental - landscape.